Differential pH Dynamics in Synaptic Vesicles From Intact Glutamatergic and GABAergic Synapses - Herman, Melissa A.; Trimbuch, Thorsten; Rosenmund, Christian (Frontiers in Synaptic Neuroscience, 2018)
Synaptic transmission requires the presynaptic release of neurotransmitter from synaptic vesicles (SVs) onto the postsynaptic neuron. Vesicular neurotransmitter transporter proteins, which use a V-ATPase-generated proton gradient, play a crucial role in packaging neurotransmitter into SVs. Recent work has revealed different proton dynamics in SVs expressing the vesicular glutamate transporter (VGLUT) or the vesicular GABA transporter (VGAT) proteins. At the whole synapse level, this results in different steady-state pH and different reacidification dynamics during SV recycling (Egashira et al., 2016). In isolated SVs, the presence of VGAT causes a higher steady state pH, which is correlated with a faster proton efflux rate (Farsi et al., 2016). To address whether proton efflux from GABAergic and glutamatergic SVs in intact synapses differs, we applied a glutamatergic- or GABAergic neuron-specific expression strategy (Chang et al., 2014) to express a genetically encoded pH sensor and/or light-activated proton pump (pHoenix; (Rost et al., 2015). We confirm that the pH profile of recycling GABAergic SVs differs from that of recycling glutamatergic SVs (Egashira et al., 2016). Using light-activation of pHoenix in pH-neutral vesicles, we demonstrate that despite dramatic differences in reacidification dynamics, the filling rate of empty glutamatergic or GABAergic SVs is similar. Finally, by investigating the pH dynamics of actively filling vesicles using pHoenix, we could show that proton efflux from GABAergic SVs is indeed initially faster than glutamatergic SVs in intact synapses.